Knowledge Transfer and Expansion of the Bio-waste Disposal System Using Black Soldier Fly Larvae in Chiang Klang District, Nan Province, Thailand - Phimolsiripol, Yuthana; Boonchuay, Pinpanit; Roskhrua, Piyanuch; Kulsarin, Jiraporn; Uthaisripadungkul, Chonthicha; Sahaschat, Piyachat; Sitthitrai, Kamonporn; Chotinun, Suwit; Chiawsuwan, Montree (Area Based Development Research Journal, 2024)
Chiang Klang District, Nan Province, faces challenges in bio-waste management, including insufficient cooperation in waste separation, inadequate budget and personnel, and an incomplete waste disposal system that does not cover all areas. This research aims to disseminate knowledge and expand the implementation of Black Soldier Fly Larvae (BSFL) cultivation for bio-waste disposal in Chiang Klang District by establishing learning processes and knowledge management. The goal is to enhance the community’s knowledge acquisition capabilities and create prototype learning spaces for innovation with 50 selected community innovators. The study began by providing education on the nutritional aspects of BSFL, cultivation techniques, housing and equipment management, harvesting, and the application of BSFL as an ingredient in animal feed. This was accomplished through expert lectures, study visits, hands-on practice, and instructional videos. The next steps involved conducting a nutritional analysis of the BSFL produced by the community to evaluate its application as an animal feed ingredient, designing a bio-waste management system at the prototype farm in Nan Province, and enhancing prototype farm housing to comply with hygiene principles. The study produced five instructional videos. Additionally, the cultivated BSFL met quality standards as a high-protein feed ingredient for egg-laying hens and indigenous chickens. Utilizing BSFL as feed for egg-laying hens and indigenous chickens reduced production costs by 3.13 Baht (around 0.085 USD) per egg and 30.12 Baht (around 0.82 USD) per kilogram, respectively, and increased income from vegetable cultivation by 61%. The community participated in designing infrastructure layouts that align with the local context. Ten prototype farms were established to expand results and create learning networks in the area. Collaborative policy recommendations were developed with the Chiang Klang Subdistrict Municipality to ensure the sustainability and longevity of the waste management system employing BSFL. Furthermore, cooperation with the National Bureau of Agricultural Commodity and Food Standards was conducted to expand results and promote the utilization of BSFL.